PARASITES IN REPTILES OF THE CONSERVATION AND REHABILITATION CENTER FOR WILDLIFE ANIMALS OF AN PUBLIC UNIVERSITY-BRAZIL - Tietz Marques, Sandra Márcia (2021)
The medical clinic for reptiles has grown in recent years, whether for attending free-living animals in rehabilitation centers or for pets. The knowledge of the parasitic fauna of the Reptilia Class is important for the identification of pathogenic agents and effective therapy. Fecal samples were collected from 35 animals of the Orders Crocodylia (N=3), Squamata (N=3) and Testudines (N=29) attended from 2013 to 2018 at the Center for Conservation and Rehabilitation of Wild Animals (PRESERVAS) of the Universidade Federal do Rio Grande do Sul (UFRGS). Fecal samples were processed by the methods of Willis, Lutz and Sheather at the Laboratory of Helminthology at UFRGS. The percentage of positive samples was 17.14% (6/35): three Trachemys dorbogni (Duméril & Bibron 1835) presenting Serpinema spp., Physaloptera spp. and Strongyloidea, respectively; two Caiman latirostris (Daudin, 1802) with Strongyloides spp. and Augusticaecum spp., respectively, and Iguana iguana (Linnaeus, 1758) with Eimeria spp. This study expands the list of parasites in reptiles from the state of Rio Grande do Sul.